Urgency of early traffic education: A systematic review of Indonesian policy implementation - Wida Widaningsih; Deni Darmawan; Khammateliev Dostnazar Omonovich; Burieva Kibrio Ergashevna (Curricula: Journal of Curriculum Development, 2025)
The high rate of traffic accidents in Indonesia involving children underscores the urgent need for preventive strategies, such as early traffic education, which is not yet systematically integrated into the national curriculum. This study systematically reviews existing policies and the implementation of early traffic education in Indonesia, comparing them with international best practices to propose an integrated framework for improvement. A systematic literature review was conducted on sources from 2019 to 2025, utilizing VOSviewer for a bibliometric analysis to map thematic clusters from relevant articles. The analysis revealed four dominant themes, with a central finding being the lack of structural integration of traffic education in Indonesian schools, which contrasts sharply with the successful interactive models abroad. The findings underscore the urgency of embedding traffic education into the formal curriculum as a component of character building. Key recommendations include formulating a national policy, enhancing teacher training with active learning methods, developing contextual media, and fostering cross-sectoral collaboration to cultivate a sustainable road safety culture.   Abstrak Tingginya angka kecelakaan lalu lintas di Indonesia yang melibatkan anak-anak menyoroti kebutuhan mendesak akan strategi preventif seperti pendidikan lalu lintas usia dini, yang belum terintegrasi secara sistematis ke dalam kurikulum nasional. Penelitian ini bertujuan meninjau secara sistematis kebijakan dan implementasi pendidikan lalu lintas usia dini di Indonesia, membandingkannya dengan praktik terbaik internasional untuk mengusulkan kerangka kerja terpadu. Kajian literatur sistematis dilakukan terhadap sumber dari tahun 2019 hingga 2025, dengan memanfaatkan VOSviewer untuk analisis bibliometrik guna memetakan klaster tematik dari artikel relevan. Analisis mengungkapkan empat tema dominan, dengan temuan utama berupa tidak adanya integrasi struktural pendidikan lalu lintas di sekolah Indonesia, yang sangat kontras dengan model interaktif yang berhasil di luar negeri. Temuan ini menggarisbawahi urgensi untuk memasukkan pendidikan lalu lintas ke dalam kurikulum formal sebagai komponen pembentukan karakter. Rekomendasi utama mencakup perumusan kebijakan nasional, peningkatan pelatihan guru dengan metode pembelajaran aktif, pengembangan media kontekstual, dan pembinaan kolaborasi lintas sektor untuk menumbuhkan budaya keselamatan jalan yang berkelanjutan. Kata Kunci: budaya keselamatan jalan; integrasi kurikulum; pendidikan lalu lintas usia dini